2019
DOI: 10.2134/jeq2019.02.0060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Hydrologic Response in Tile‐Drained Landscapes: Implications for Phosphorus Transport

Abstract: Phosphorus (P) loss in agricultural discharge has typically been associated with surface runoff; however, tile drains have been identified as a key P pathway due to preferential transport. Identifying when and where these pathways are active may establish high‐risk periods and regions that are vulnerable for P loss. A synthesis of high‐frequency, runoff data from eight cropped fields across the Great Lakes region of North America over a 3‐yr period showed that both surface and tile flow occurred year‐round, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 43 publications
5
47
0
Order By: Relevance
“…Our results provide insight into how preferential flow contributions are affected by desiccation crack networks that bypass the drainage layer during the growing season. Surface runoff was second greatest in the summer, which agrees well with other recent studies that have shown that high‐intensity rainfall on clay soils can trigger infiltration‐excess surface flow with either simultaneous or zero tile response (e.g., Kokulan, Macrae, Lobb, & Ali, 2019; Macrae et al., 2019). We found that quickflow contributions constituted 80% of tile flow during summer months, suggesting simultaneous connectivity of surface and tile pathways, which occurs in spring and summer in clay soils (Macrae et al., 2019).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results provide insight into how preferential flow contributions are affected by desiccation crack networks that bypass the drainage layer during the growing season. Surface runoff was second greatest in the summer, which agrees well with other recent studies that have shown that high‐intensity rainfall on clay soils can trigger infiltration‐excess surface flow with either simultaneous or zero tile response (e.g., Kokulan, Macrae, Lobb, & Ali, 2019; Macrae et al., 2019). We found that quickflow contributions constituted 80% of tile flow during summer months, suggesting simultaneous connectivity of surface and tile pathways, which occurs in spring and summer in clay soils (Macrae et al., 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Field‐scale nutrient studies in tile‐drained agroecosystems have evolved over the past 50 yr and now focus on methodologies for continuous monitoring of flow‐weighted mean concentrations (FWMCs) of dissolved and total nutrient species using automated samplers on surface flumes and subsurface tile mains (Harmel et al., 2018; Williams et al., 2016). Temporal and economic constraints often limit analyses that can be performed on samples, and, as a result, most long‐term monitoring programs typically only analyze bioavailable nutrients (orthophosphate, nitrate, and ammonium) and total nutrient concentrations (Christianson et al., 2016; Macrae, English, Schiff, & Stone, 2007; Macrae et al., 2019; Reba et al., 2013; Williams et al., 2016). Regarding total nutrients, both alkaline and alkaline/acid persulfate digestions on unfiltered samples have been used for coupled measurements of total P (TP) and total N (TN), although the alkaline persulfate digestions are recognized to underpredict TP when suspended sediment concentrations are significant (Dayton, Whitacre, & Holloman, 2017; Koroleff, 1983; Patton & Kryskalla, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The observed events accounted for ∼58% of annual flow at the clay site, and 38% of annual flow at the loam site during the study period (Macrae et al., 2019). The events covered a wide range of event types (e.g., snowmelt without rain, convection storms, rain on snow), event sizes, and seasons and were therefore an accurate and strong representation of climate and processes in the Great Lakes region.…”
Section: Resultsmentioning
confidence: 99%
“…Two sites in the Lake Erie watershed that have been used for ongoing agricultural runoff research (Macrae et al, 2019;Plach et al, 2019;Van Esbroeck, Macrae, Brunke, & McKague, 2016) were selected for further monitoring of preferential flow (Figure 1). One site, located near Essex, ON, was characterized by mesic Typic Argiaquoll clay soil (hereafter referred to as clay of 900 mm (10% as snow) and 1,024 mm (30% as snow) (ECCC, 2019).…”
Section: Study Sitesmentioning
confidence: 99%
“…This leads Smith et al (2019) to highlight the challenges of applying science to agricultural management, and call into question “one‐size‐fits‐all” approaches. Macrae et al (2019), for example, examine the activation of surface runoff and tile flow as pathways of P transport and demonstrate that region‐specific soil type and seasonality need to be considered when designing management strategies to decrease P loading via tile drains.…”
Section: Focusing On Place‐based Solutions: Think Globally Act Locallymentioning
confidence: 99%